2016
DOI: 10.1080/21505594.2016.1140297
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic switching ofCandida tropicalisis associated with cell damage in epithelial cells and virulence inGalleria mellonellamodel

Abstract: (2016) Phenotypic switching of Candida tropicalis is associated with cell damage in epithelial cells and virulence in Galleriamellonella model, Virulence, 7:4,[379][380][381][382][383][384][385][386]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 24 publications
2
16
0
Order By: Relevance
“…Macromorphology was examined following the reactivation of the irradiated yeast in 2 mL of Yeast Peptone Dextrose (YPD) liquid medium and incubated at 25 °C for 24 h. The inoculum was adjusted to a density of approximately 300 CFU/mL, uniformly seeded on plates containing YPD agar medium and maintained at room temperature for 96 h. The colonies were photographed under a digital microscope. The ultrastructure of the colony was analyzed by scanning electron microscopy (SEM) after lyophilization in accordance with Moralez et al [ 14 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Macromorphology was examined following the reactivation of the irradiated yeast in 2 mL of Yeast Peptone Dextrose (YPD) liquid medium and incubated at 25 °C for 24 h. The inoculum was adjusted to a density of approximately 300 CFU/mL, uniformly seeded on plates containing YPD agar medium and maintained at room temperature for 96 h. The colonies were photographed under a digital microscope. The ultrastructure of the colony was analyzed by scanning electron microscopy (SEM) after lyophilization in accordance with Moralez et al [ 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…C. tropicalis from clinical isolates naturally exhibits highly diversified macromorphological variations known as phenotypic switching [ 12 , 13 ], an ability associated with cell damage in epithelial tissue. Although this virulence attribute has been observed in animal model [ 14 ], it is not known if the same occurs in humans. It is also not known if yeast exposed to radiation suffer changes in their putative virulence factors.…”
Section: Introductionmentioning
confidence: 99%
“…Concerning virulence fungal assays, studies have been reported using G. mellonella as an infection model for different Candida species (Scorzoni et al, 2013; Frenkel et al, 2016; Moralez et al, 2016), Cryptococcus spp. (Benaducci et al, 2016), Sporothrix schenckii (Clavijo-Giraldo et al, 2016), Paracoccidioides spp.…”
Section: Alternative Animal Models To Study Fungal Virulence and Antimentioning
confidence: 99%
“…Galleria mellonella models have become invaluable to study cellular and humoral immune responses against pathogens [3133], epigenetic influences on the evolution of virulence [32,34,35], and for development and testing antimicrobials [3639]. It is relevant to add that the complete genomes of P. destructans and G. mellonella have become available recently [40,41].…”
Section: Resultsmentioning
confidence: 99%